Incidence of Vaccine-Preventable Childhood Diseases in the European Union and in the European Free Trade Association Countries - Jachowicz, Estera; Gębicka, Magdalena; Plakhtyr, Daria; Shynkarenko, Myroslav; Urbanowicz, Juri; Mach, Maciej; Czepiel, Jacek; Marchewka, Jakub; Wójkowska-Mach, Jadwiga (Vaccines (Basel), 2021)
Introduction: Despite the widespread availability of vaccines, the incidence of vaccine-preventable childhood diseases (VPCD) started to grow in recent years. The aim of the study was to compare the annual incidence of selected VPCDs in the EU (European Union) and EFTA (European Free Trade Association) countries in the period of the last 5 years (2014–2019 or other intervals, depending on data availability), and the country-specific vaccine schedules. Methods: VPCD incidence rates in Europe were based on “The Surveillance Atlas of Infectious Diseases” by the ECDC (European Centre for Disease Prevention and Control); vaccination schedules were based on ECDC reports. Results: The obligation to vaccinate was not universal, and it generally only applied to two preparations: the MMR (measles, mumps, rubella) vaccine and the one against polio. During the study, the situation associated with mumps did not change or improve in individual countries; the median incidence amounted to 30 cases. The median incidence associated with rubella amounted to 1 case, but in a few countries, it grew very rapidly, i.e., in Germany, Italy, and Romania; in Poland, the incidence was clearly decreasing, from 5923 to 1532 cases. The most dynamic situation concerned measles. The total median was 2.4 cases per 100,000 population; the only one country with falling incidence was Germany. The diseases associated with Streptococcus pneumoniae and Neisseria meningitidis remained at a stable level in all analyzed countries. Conclusion: Vaccine schedules differ among the countries, so does the epidemiological situation of selected diseases. Morbidity on measles was the most disturbing phenomenon: the incidence rate increased in almost 40% of all countries, regardless of the obligation to vaccinate. The increasing incidence of VPCD may be due to anti-vaccine movements, the activity of which is often caused by mistrust and spreading misinformation. In order to better prevent the increase in morbidity, standardization of vaccine schedules and documentation should be considered in the EU countries.